THE PROPHET MUHAMMAD ﷺ AS THE FIRST PRACTITIONER OF ISLAMIC PSYCHOLOGY: A CRITICAL ANALYSIS OF THE PROPHETIC THERAPEUTIC METHADOLOGY (Al-Aasar, 2026)
This article examines the Prophet Muhammad ﷺ as the founding and most complete practitioner of Islamic psychology, arguing that his methodology of engaging human psychological suffering anticipated, by fourteen centuries, the core principles of contemporary evidence-based psychotherapy. Drawing upon authenticated Hadith literature, classical Islamic scholarship, and contemporary psychological research, the article demonstrates that the Prophetic therapeutic methodology was characterized by six distinct principles: individualized assessment, gradual behavioral change, holistic engagement of the whole person, unconditional therapeutic regard, the therapeutic management of diseases of the heart, and the construction of a healing community. Each principle is demonstrated through specific documented incidents from the Sunnah and analyzed against its modern clinical equivalent. The article concludes that the convergence between Prophetic methodology and contemporary psychological research is not coincidental but reflects the foundational Islamic conviction that divine revelation reveals what the human being genuinely needs, a claim that contemporary neuroscience and clinical psychology are independently and incrementally confirming.